Evolution of Cerebral Ischemia Assessed by Amide Proton Transfer-Weighted MRI - Song, Guodong; Li, Chunmei; Luo, Xiaojie; Zhao, Xuna; Zhang, Shuai; Zhang, Yi; Jiang, Shanshan; Wang, Xianlong; Chen, Yuhui; Chen, Haibo; Gong, Tao; Zhou, Jinyuan; et al. (Frontiers in Neurology, 2017)
Amide Proton Transfer-weighted (APTW) MRI has recently become a potentially important tool for evaluating acidosis in ischemic stroke. The purpose of this study was to evaluate the dynamic pH-related changes in the lesions in patients with ischemia. Thirty-nine patients with ischemic stroke (symptom onset to imaging time ranging 2 hours - 7 days) were examined with a 3.0 T MRI system. Patients were divided into four groups: at the hyperacute stage (onset time ≤ 6 hours), at the acute stage (6 hours < onset time ≤ 48 hours), at the early subacute stage (48 hours < onset time ≤ 96 hours), and at the late subacute stage (96 hours < onset time ≤ 168 hours). The APTW signal intensities were quantitatively measured in multiple ischemic regions for each patient. Compared with the contralateral normal white matter, APTW signals were significantly lower in ischemic tissue for all four stages (P < 0.05). The APTW signal intensities (APTWave and APTWmin) increased consistently with onset time (R2 = 0.11, P = 0.040; R2 = 0.13, P = 0.022; respectively). APTWmax-min showed a continued reduction with onset time (R2 = 0.44, P < 0.001). Our results suggest that persistent tissue acidification could occur after ischemia, and as the time from stroke onset increases, the acidotic environment would alleviate. APTW signal intensities could reflect pH-weighted properties in ischemic tissue at different stages and time points.